Ultrafast electron dynamics in epitaxial graphene investigated with time- and angle-resolved photoemission spectroscopy. (2nd April 2015) - Ulstrup, Søren; Christian Johannsen, Jens; Crepaldi, Alberto; Cilento, Federico; Zacchigna, Michele; Cacho, Cephise; Chapman, Richard T; Springate, Emma; Fromm, Felix; Raidel, Christian; Seyller, Thomas; Parmigiani, Fulvio; et al.
Abstract: In order to exploit the intriguing optical properties of graphene it is essential to gain a better understanding of the light-matter interaction in the material on ultrashort timescales. Exciting the Dirac fermions with intense ultrafast laser pulses triggers a series of processes involving interactions between electrons, phonons and impurities. Here we study these interactions in epitaxial graphene supported on silicon carbide (semiconducting) and iridium (metallic) substrates using ultrafast time- and angle-resolved photoemission spectroscopy (TR-ARPES) based on high harmonic generation. For the semiconducting substrate we reveal a complex hot carrier dynamics that manifests itself in an elevated electronic temperature and an increase in linewidth of the π band. By analyzing these effects we are able to disentangle electron relaxation channels in graphene. On the metal substrate this hot carrier dynamics is found to be severely perturbed by the presence of the metal, and we find that the electronic system is much harder to heat up than on the semiconductor due to screening of the laser field by the metal.